2020
DOI: 10.1002/joc.6695
|View full text |Cite
|
Sign up to set email alerts
|

Atlantic Meridional Overturning Circulation reconstructions and instrumentally observed multidecadal climate variability: A comparison of indicators

Abstract: The Atlantic Meridional Overturning Circulation (AMOC) has an important role in the Earth's climate system, but it remains unclear how the instrumentally observed multidecadal variability of the Earth's climate is related to the AMOC. We carried out a comprehensive evaluation of five representative indicators of the AMOC, including one atmospheric index based on the effect of accumulated atmospheric forcing on the AMOC and four oceanographic indices using surface and subsurface oceanographic variables in the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 91 publications
6
19
0
Order By: Relevance
“…AMOC is usually seen as influencing the AMO (Marini and Frankignoul, 2014;Zhang et al, 2019) but two-way oscillatory relationships have been observed in model studies (Zhang and Wang, 2013;Kim et al, 2021). The recent changes in a range of surface variables that show a relationship between Atlantic multidecadal variability and AMOC are consistent with recent direct estimates of AMOC flow volumes (Sun et al, 2021).…”
Section: Decadal Oscillations and Network Behavioursupporting
confidence: 58%
See 1 more Smart Citation
“…AMOC is usually seen as influencing the AMO (Marini and Frankignoul, 2014;Zhang et al, 2019) but two-way oscillatory relationships have been observed in model studies (Zhang and Wang, 2013;Kim et al, 2021). The recent changes in a range of surface variables that show a relationship between Atlantic multidecadal variability and AMOC are consistent with recent direct estimates of AMOC flow volumes (Sun et al, 2021).…”
Section: Decadal Oscillations and Network Behavioursupporting
confidence: 58%
“…If considered as part of a self-regulating complex system, this role becomes even more important. The AMO is understood to be linked to AMOC (Kim et al, 2021;Sun et al, 2021) and telecommunicates with the northern and tropical Pacific (Sun et al, 2017).…”
Section: Decadal Oscillations and Network Behaviourmentioning
confidence: 99%
“…AMOC is generally seen as influencing the AMO (Marini and Frankignoul, 2014;Zhang et al, 2019) but two-way oscillatory relationships have been observed in model studies (Kim et al, 2021) including CMIP5 models (Zhang and Wang, 2013). The recent changes in a range of surface variables that show a relationship between Atlantic multidecadal variability and AMOC are consistent with recent direct estimates of AMOC flow volumes (Sun et al, 2021). The stability of AMOC is very much a matter of debate, but simple and intermediate models produce abrupt phase transitions (Dijkstra, 2019;Johnson et al, 2019), while more complex models produce a wide range of responses, showing high sensitivity to the background state (Johnson et al, 2019).…”
Section: Atlantic Meridional Overturning Circulationsupporting
confidence: 55%
“…It is also suggested that the AMOC has profound influences on the multidecadal changes in the Atlantic basin and adjacent areas via anomalous ocean heat transport (Buckley & Marshall, 2016; Trenberth & Caron, 2001). It has been pointed out that the NAO forces the AMOC, transporting heat across the Atlantic basin, and eventually affects the surface air temperature and precipitation anomalies on multidecadal time scales (Sun et al., 2020; J. Zhang et al., 2021). Since the Atlantic hurricanes are favored by warm SST associated with positive ocean heat transport (R. Zhang et al., 2019), the AMOC and TC activity are thus closely related.…”
Section: Introductionmentioning
confidence: 99%